Real time traffic monitoring system using crowd sourced GPS data - Md. Al Amin; Uddin, Md. Rofi (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2015.